2008
DOI: 10.1007/s00259-008-0987-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of (R)-[11C]PK11195 binding in rheumatoid arthritis

Abstract: Purpose Rheumatoid arthritis (RA) involves migration of macrophages into inflamed areas. (R)-[11 C]PK11195 binds to peripheral benzodiazepine receptors, expressed on macrophages, and may be used to quantify inflammation using positron emission tomography (PET). This study evaluated methods for the quantification of (R)- Conclusion (R)-[11 C]PK11195 kinetics in the knee were best described by a reversible single-tissue compartment model including blood volume. Applying metabolite corrections did not increase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
(37 reference statements)
2
17
1
Order By: Relevance
“…The close similarity of the V T estimates indicates the negligible effect of labeled metabolites in these 2 small cohorts of patients. The same conclusion was reached by Kropholler et al in their study on the inflammation of knee joints in patients with rheumatoid arthritis using 11 C-(R)-PK11195 (22). The advantage of this approach is the simplification of the acquisition protocol, obviating the sampling and measurement of radiolabeled compounds in plasma.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The close similarity of the V T estimates indicates the negligible effect of labeled metabolites in these 2 small cohorts of patients. The same conclusion was reached by Kropholler et al in their study on the inflammation of knee joints in patients with rheumatoid arthritis using 11 C-(R)-PK11195 (22). The advantage of this approach is the simplification of the acquisition protocol, obviating the sampling and measurement of radiolabeled compounds in plasma.…”
Section: Discussionsupporting
confidence: 53%
“…The subsequent appearance of radiolabeled metabolites has only a small effect on the POB ratio, suggesting a similar partitioning of 11 C-(R)-PK11195 radioactivity and its radiolabeled metabolites between plasma and red blood cells. The POB ratio obtained in venous arterialized blood is approximately 10% smaller than the mean POB ratio of 1.55 reported by Kropholler et al for measurements obtained in arterial blood (22). In Figure 2, measurements of the parent fraction in plasma from previous studies with 11 C-(R)-PK11195 in humans (32)(33)(34)(35) are shown in comparison with our results.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…For example, Kropholler et al used PET to monitor macrophage migration into inflamed areas in rheumatoid arthritis using the ligand PK11195 coupled to a PET tracer, 11 C, which binds to benzodiazepine receptors on macrophages [125].…”
Section: Future Applications Of Hybrid Imaging With New Radiotracersmentioning
confidence: 99%